Análisis del Impacto de Variables Macroeconómicas, sobre el Índice Bursátil COLCAP Durante el Período 2015 - 2019. (2022)
This work aims to show the possible relationship between the intervention interest rate of the bank of the republic (TII), which is the main tool that the Board of Directors has to influence the monetary policy of the country, the representative market rate (TRM ) which is the exchange rate between the dollar and the Colombian peso and the country's real production GDP and how these macroeconomic variables could have an impact on the COLCAP stock market index during the period of 2015 - 2019.